2022
DOI: 10.1042/cs20210507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perspectives on vagus nerve stimulation: present and future

Abstract: The vagus nerve, the great wanderer, is involved in numerous processes throughout the body and vagus nerve stimulation (VNS) has the potential to modulate many of these functions. This wide-reaching capability has generated much interest across a range of disciplines resulting in several clinical trials and studies into the mechanistic basis of VNS. This review discusses current preclinical and clinical evidence supporting the efficacy of VNS in different diseases and highlights recent advancements. Studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 120 publications
(124 reference statements)
1
16
0
2
Order By: Relevance
“…It plays a major role in maintaining autonomic tone throughout in the brain, the thorax, and the abdomen. The vagus nerve stimulation (VNS), first approved by the US Food and Drug Association (FDA) in 1997 in the form of a cervical implantable device, is currently approved for drug-resistant epilepsy, depression, and morbid obesity 2 , 3 . Further studies have shown promising results that VNS can treat disorders such as anxiety disorder, Alzheimer’s disease, cluster headache, heart failure, sepsis, lung injury, rheumatoid arthritis, inflammatory bowel disease, obesity, and diabetes 4 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a major role in maintaining autonomic tone throughout in the brain, the thorax, and the abdomen. The vagus nerve stimulation (VNS), first approved by the US Food and Drug Association (FDA) in 1997 in the form of a cervical implantable device, is currently approved for drug-resistant epilepsy, depression, and morbid obesity 2 , 3 . Further studies have shown promising results that VNS can treat disorders such as anxiety disorder, Alzheimer’s disease, cluster headache, heart failure, sepsis, lung injury, rheumatoid arthritis, inflammatory bowel disease, obesity, and diabetes 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is impossible to selectively stimulate certain fibers through conventional methods, and efferent branches are unintentionally stimulated together. Efferent branches send parasympathetic cholinergic signals to target organs, including the lungs, digestive tract, and heart 3 . The most critical reports include cardiac events, such as bradycardia and asystole, occurring in approximately 1 per 1000 cases as a result of direct stimulation of the cardiac branches of the vagus nerve 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As diseases are already or soon to be diagnosed earlier, minimally invasive VNS modalities should also be proposed as a first-line treatment in several indications [ 54 , 105 ]. Remarkably, transcutaneous auricular VNS was recently advocated for the treatment of endometriosis [ 106 ], which is especially interesting since the diagnosis of endometriosis has become available with a simple salivary test [ 107 ].…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…Left vagus nerve stimulation (LVNS) has been approved by the Food and Drug Administration (FDA) for the treatment of epilepsy, depression, migraines, cluster headaches, pain, and obesity ( 15 ). Recently, LVNS has been explored for the treatment of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Right vagus nerve stimulation (RVNS) has not been employed for the treatment of brain diseases due to its possible cardiac side effects ( 15 ). However, no studies have reported any incidences of cardiac side effects with RVNS.…”
Section: Introductionmentioning
confidence: 99%